2023
DOI: 10.1101/2023.01.13.523841
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SUMO protease FUG1, histone reader AL3 and the PRC1 Complex are integral to repeat-expansion induced epigenetic silencing inArabidopsis thaliana

Abstract: Epigenetic gene silencing induced by expanded repeats can cause diverse phenotypes ranging from severe growth defects in plants to genetic diseases such as Friedreichs ataxia in humans (1). The molecular mechanisms underlying repeat expansion-induced epigenetic silencing remain largely unknown (2,3). Using a plant model, we have previously shown that expanded repeats can induce smallRNAs which in turn can lead to epigenetic silencing through the RNA-dependent DNA methylation pathway (4,5). Here, using a geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…For example, the SUMO protease FUG1 physically interacts with AL3, and interference with its potential SUMOylation site disrupts its nuclear localization. AL3 interacts with LHP1 of the PRC1 complex, and the FUG1-AL3-LHP1 module is essential for conferring repeat amplification-associated epigenetic silencing of the SUMO protease FUG1, histone reader AL3, and PRC1 complex, which are integral to repeat expansion-induced epigenetic silencing in A. thaliana [42]. Similarly, cluster and conserved motif analyses revealed that the AL family proteins contained two conserved domains, the Alfin domain and the PHD domain (Figure 2B).…”
Section: Structural Characteristics and Classification Of The Alfin-l...mentioning
confidence: 94%
“…For example, the SUMO protease FUG1 physically interacts with AL3, and interference with its potential SUMOylation site disrupts its nuclear localization. AL3 interacts with LHP1 of the PRC1 complex, and the FUG1-AL3-LHP1 module is essential for conferring repeat amplification-associated epigenetic silencing of the SUMO protease FUG1, histone reader AL3, and PRC1 complex, which are integral to repeat expansion-induced epigenetic silencing in A. thaliana [42]. Similarly, cluster and conserved motif analyses revealed that the AL family proteins contained two conserved domains, the Alfin domain and the PHD domain (Figure 2B).…”
Section: Structural Characteristics and Classification Of The Alfin-l...mentioning
confidence: 94%